A study of Malaysian social network site user's awareness in digital legacy and its management / Amir Rahimi Mohd Azami - Mohd Azami, Amir Rahimi (2013)
This dissertation is about a study of Malaysian Social Network Site user's awareness in digital legacy and its management. The purposes of this dissertation are to investigate the level of awareness in digital legacy and its management among Social Network Site users and to suggest mechanisms to increase the issue. To investigate the level of awareness, the researcher gathered data and information through a survey to Social Network Site users, interviews with experts in legal and Islamic profession, a group interview with Social Network Site user representatives and a study on social network sites. To suggest the mechanisms, the researcher did content analysis on the literature's and adapted the approaches and tools being recommended by these literature. The researcher also suggests the mechanisms based from feedback's and discussions made with the experts and the Social Network Site user representatives. From these processes, it was concluded that the awareness level in digital legacy and its management among Malaysian Social Network Site users is at a low level as there is lack of information being given to them. Several communication channels to increase awareness in digital legacy are suggested and it is important to expose the threats of not doing digital legacy management. Methods to do digital legacy management are also suggested. This dissertation hopes to make Social Network Site users realize that their digital legacy is important and to provide them with useful tips to manage their digital legacy.